Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376675
|View full text |Cite
|
Sign up to set email alerts
|

Assessing 2D and 3D Heatmaps for Comparative Analysis

Abstract: Heatmaps are a popular visualization technique that encode 2D density distributions using color or brightness. Experimental studies have shown though that both of these visual variables are inaccurate when reading and comparing numeric data values. A potential remedy might be to use 3D heatmaps by introducing height as a third dimension to encode the data. Encoding abstract data in 3D, however, poses many problems, too. To better understand this tradeoff, we conducted an empirical study (N = 48) to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Kraus et al . [KAB*20] conducted a study on 3D heightmap visualizations for comparative analysis tasks and compared them with juxtapositioned 2D heatmaps. Their results indicate a potential benefit of immersive environments for certain comparative tasks, such as estimating the relative offset of given locations in heatmaps.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kraus et al . [KAB*20] conducted a study on 3D heightmap visualizations for comparative analysis tasks and compared them with juxtapositioned 2D heatmaps. Their results indicate a potential benefit of immersive environments for certain comparative tasks, such as estimating the relative offset of given locations in heatmaps.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in the comparative analysis of 3-D distri butions of abstract dat a, t he immersive, spatialized 3-D variant with superpositioned 3-D heatmaps was superior to t he juxtapositioned 2-D variant in certain tasks. 8 As shown in Figure 5, the vertical layout combined with the encoding of values on heightmaps facilitates the comparison of the two distributions. The user can slide one dist ribution through the other to identify correlations, offset s, and general trends.…”
Section: Presentationmentioning
confidence: 99%
“…FIGURE5. Abstract data are spatialized, displayed as stacked 3-D heightmaps, and observed in VR for comparative analysis 8. …”
mentioning
confidence: 99%
“…For instance, Donalek et al reported a better perception of the datascape geometry in graph visualizations when participants were immersed in VR [ 45 ]. Further benefits have been identified in terms of data validation [ 46 ], collaboration [ 45 ], increased task performance on specific data exploration tasks [ 47 , 48 ], and memorability [ 49 ]. Etemadpour et al found that especially surface-based visual encodings profited from a stereoscopic perception in VR [ 50 ].…”
Section: Related Workmentioning
confidence: 99%